2003
DOI: 10.1038/sj.ejcn.1601581
|View full text |Cite
|
Sign up to set email alerts
|

Is underweightness still a major problem in Parkinson's disease patients?

Abstract: Objective: To evaluate the current rate of underweightness amongst Parkinson's disease (PD) patients at an Italian referral centre. Design: Epidemiological study on consecutive patients presenting for the first time in a 16-month period. Setting: Nutritional service of PD referral centre in Milan, Italy. Subjects: Three-hundred and sixty-four PD patients diagnosed according to CAPIT criteria. Methods: Anthropometric assessments: BMI and waist-to-hip ratio; evaluation of therapeutic physical activity (h=week). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 19 publications
4
42
2
Order By: Relevance
“…Furthermore a study on IPD patients in our catchment area (Region of Lombardy) found no evidence of BMI differences between Parkinsonians and the normal population. 13 The main findings of our study are plausibly explained by the reduced sympathetic activity amply documented in IPD. The sympathetic nervous system is permanently active in maintaining homeostasis, and is further activated during stress, physical activity, and whenever the body is stimulated.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore a study on IPD patients in our catchment area (Region of Lombardy) found no evidence of BMI differences between Parkinsonians and the normal population. 13 The main findings of our study are plausibly explained by the reduced sympathetic activity amply documented in IPD. The sympathetic nervous system is permanently active in maintaining homeostasis, and is further activated during stress, physical activity, and whenever the body is stimulated.…”
Section: Discussionmentioning
confidence: 49%
“…Van der Marck et al have concluded that PD patients have a significantly lower body mass index (BMI) than controls in a meta-analysis [28], but Barichella et al have reported that nutrition is generally normal in PD patients [29]. So it needs further research to explore the relationship between nutrition and the changes of lipids and lipoproteins in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Today, in spite of a decreased average BMI, individual PD patients may be overweight (75). In fact, prevalence of overweight in PD was reported to be about 60% in Italy (105) and 50% in Germany (80). In France and USA, more than 50% of the patients selected for DBS, i.e., patients with advanced disease suffering from motor complications presented an overweight with a BMI >25 kg/m 2 (106108).…”
Section: Parkinson’s Diseasementioning
confidence: 99%